Buerger Allen Method Training to Increase Ankle Brachial Index (ABI) of Type 2 Diabetes Mellitus Patients in the Aras Kabu Community - Simarmata, Juni Mariati; Angriawan, Angriawan; Syara, Arfah May; Waruwu, Ria Apriliani (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2024)
Prevention of diabetes mellitus complications can be done through joint movement exercises, which can be effective, efficient, and minimal risk through Buerger Allen Exercise. ABI describes the severity of peripheral arterial disease in DM patients. ABI measurements are carried out on systolic arm and systolic leg pressures. Buerger Allen Exercise is able to improve peripheral circulation of the lower extremities. This training activity aims to educate and train people at the Kabu level so that they can apply Buerger Allen Exercise with increasing knowledge. Training activities involve a series of processes through providing materials, demonstrations, training, and questions and answers. PkM participants are people from the Aras Kabu sub-district represented by 20 participants. The instruments used include Teaching Aids, Laptops, Infocus, SOPs. The increase in knowledge and skills of PkM participants is measured based on the increase in post-test scores compared to pre-test scores. Buerger Allen Method Training has been proven to be able to reduce ABI rates to the mild category by 60%, which was initially only 35%. In addition, PkM participants have understood the theory of Buerger Allen, ABI, and its benefits for type 2 DM patients. PKM participants are also able to apply Buerger Allen exercises according to SOP. PkM training activities provide benefits in the form of increasing the knowledge and skills of PkM participants, which is confirmed through the post-test knowledge value being categorized as good and very good.